2007
DOI: 10.1016/j.jaad.2006.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Reply

Abstract: 2. Rushton DH, Dover R, Sainsbury AW, Norris MJ, Gilkes JJH, Ramsay ID. Why should women have lower reference limits for hemoglobin and ferritin concentrations than men? BMJ 2001;322:1355-7. 3. Waalen J, Felitti V, Beutler E. Hemoglobin and ferritin concentrations in men and women: cross sectional study. BMJ 2002; 325:137. 4. Guyatt GH, Oxman AD, Ali M, William A, Mcllroy W, Patterson C. Laboratory diagnosis of iron deficiency anemia. J Gen Intern Med 1992;7:145-53. 5. Puolakka J. Serum ferritin in the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In our article, we showed that many forms of hair loss may be related to nonanemic iron deficiency. 4 If this is indeed the case, what other diseases may be affected by nonanemic iron deficiency? Also, what other therapies…”
Section: Replymentioning
confidence: 99%
“…In our article, we showed that many forms of hair loss may be related to nonanemic iron deficiency. 4 If this is indeed the case, what other diseases may be affected by nonanemic iron deficiency? Also, what other therapies…”
Section: Replymentioning
confidence: 99%